The perceived social rejection of sexual minorities: Substance use and unprotected sexual intercourse - Nick Drydakis (Global Labor Organization (GLO), 2022)
This study presents associations between the perceived social rejection of sexual minorities and tobacco, alcohol, and cannabis consumption and unprotected sexual intercourse in the capital of Greece, Athens. This is the first Greek study to evaluate the concept of the minority stress theory on sexual minorities' substance use and unprotected sexual intercourse. In addition, this is among the first international studies to examine whether periods of adverse economic conditions are associated with sexual minorities' substance use and unprotected sexual intercourse. Two panel datasets covering the periods 2013-2014 and 2018-2019 were used to determine the perceived social rejection, that is, whether sexual minorities have been rejected by friends, treated unfairly in educational and/or workplace environments, treated negatively in social situations and received poor health and public services due to their sexuality. The estimates indicate that perceived social rejection is associated with the increased consumption of tobacco (by 9.1%, P ﹤0.01), alcohol (by 7.1%, P ﹤0.01), and cannabis (by 12.5%, P ﹤0.01), as well as unprotected sexual intercourse (by 6.5%, P ﹤0.01). In the first three cases, the magnitude of the associations is stronger for men than women and there is increased cannabis consumption during periods of deteriorated economic conditions (by 5.5%, P ﹤0.01). In the European Union, reducing stigma, substance use, risky sexual behaviours, and health inequalities for sexual minorities is a goal of public health. If minority stress is correlated with substance use and risky sexual behaviours leading to detrimental physical/mental health outcomes then prevention and support interventions should be designed.
Keywords: I12; I14; L66; 330; Sexual orientation; Minority stress; Smoking; Drinking; Cannabis; Unprotected sexual intercourse; Economic recession